1990
DOI: 10.1111/j.1365-2621.1990.tb03582.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Variety, Maturity and Processing on Pear Juice Quality and Protein Stability

Abstract: d'Anjou, Cornice, and Bartlett pears were processed into clarified juices from hard green and soft ripened fruits. Processing trials with and without SOz were conducted. Effects of variety, maturity and processing on browning, turbidity, proteins, and stability were investigated. Browning increased with heat treatment, and was reduced by processing with SOz. Total soluble protein content increased with fruit maturity and processing with SO*. Protein fractions from a clarifying enzyme preparation (mainly arabin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…These authors also reported an increase in turbidity during storage. Fining helps remove active precursors and thus, decrease the potential for haze formation during storage, while providing a more limpid juice (Hsu et al, 1987(Hsu et al, , 1989(Hsu et al, , 1990.…”
Section: Turbiditymentioning
confidence: 98%
“…These authors also reported an increase in turbidity during storage. Fining helps remove active precursors and thus, decrease the potential for haze formation during storage, while providing a more limpid juice (Hsu et al, 1987(Hsu et al, , 1989(Hsu et al, , 1990.…”
Section: Turbiditymentioning
confidence: 98%
“…Table 2 indicates the specificity of the excised spots (last column: spot specificity). For instance, 8,6, and 15 spots were specific to protocol 1, 2, and 4, respectively. All the 44 spots excised from 2-D pattern corresponding to protocol 3 were present on 2-D pattern from protocol 4 as well.…”
Section: Protein Identificationmentioning
confidence: 99%
“…To our knowledge, Hsu and Heatherbell [6] were the first to use such a technique and were able to isolate up to 41 proteins on silver nitratestained 2-D gels from Gewürztraminer fruits, juice, and wine. In 1992, Tesniere and Robin [7] adapted Hsu and Heatherbell's protocol to study proteins from mature red berries; they could visualize up to 52 spots on silver nitrate-stained 2-D gels.…”
Section: Introductionmentioning
confidence: 98%
“…To obtain a completely transparent liquid, the first step is to destabilize the dispersion. This procedure also helps to remove active haze precursors, decreasing the potential for haze formation during storage and providing a more limpid juice (Hsu et al, 1987(Hsu et al, , 1989(Hsu et al, , 1990. Therefore, the fining step is an important procedure that should be carefully controlled during the processing of clarified apple juice.…”
Section: Introductionmentioning
confidence: 99%